Psychiatric symptoms subsequent to COVID-19 and their association with clinical features: A retrospective investigation. (October 2022) - Fiabane, Elena; Pain, Debora; Aiello, Edoardo Nicolò; Radici, Alice; Manera, Marina Rita; Grossi, Federica; Ottonello, Marcella; Pistarini, Caterina
Highlights: Anxiety, depression and PTSD symptoms do occur in COVID-19-recovered individuals. Neither cognitive nor clinical variables are related to such disturbances. Psychiatric symptoms might occur net or premorbid at-risk status for brain disorders. Abstract: This study explores the association between psychiatric symptoms following COVID-19 and demographic, disease-related and premorbid clinical confounders. Global cognition, depression, anxiety and PTSD features were assessed in 152 post-COVID-19 patients, subdivided into being at risk for brain disorders or not. In both groups, clinically meaningful depression, anxiety and PTSD symptoms were mildly-to-moderately frequent (4−45%). No demographic or clinical variables predicted psychiatric measures (except for lower age predicting higher anxiety levels). Depression, anxiety and PTSD measures were associated among each other. Hence, depression-, anxiety- and PTSD- spectrum disturbances in COVID-19 survivors are likely to be unassociated with disease-related and premorbid features.